From prospecting to mining: A review of enabling technologies, LCAs, and LCCAs for improved construction and demolition waste management. (15th March 2023) - Jiang, Jingbo; Chu, Chunli; Song, Lulu; Gao, Xiaofeng; Huang, Beijia; Zhang, Yufei; Zhang, Yi; Liu, Ying; Hou, Lijing; Ju, Meiting; Cao, Zhi
Highlights: Current and emerging urban mining technologies are identified. LCA and LCCA results on construction and demolition waste management are reviewed. Modeling of the potentials and costs of urban mining technologies is evaluated. Opportunities to improve LCA and LCCA in C&DW decision-making are discussed. Abstract: Knowledge gained from anthropogenic resource prospecting can shed light on the theoretical potential of secondary resources stored in anthropogenic systems. Among others, secondary resources accumulated in the built environment account for a big fraction of anthropogenic resources, indicating great potential for urban mining. However, realizing these opportunities and developing urban mining strategies will require a comprehensive understanding of the technical viability of urban mining technologies, and how their implementation will affect the technical, economic, and environmental performance of a construction and demolition waste (C&DW) management system. To address these important issues, this review summarizes (1) current and emerging technologies that can enable the transition from anthropogenic resource prospecting to anthropogenic resource mining, (2) Life Cycle Assessment (LCA) and Life Cycle Cost Analysis (LCCA) results to date on various C&DW management systems, (3) key parameters that govern the technical, economic, and environmental performance of a C&DW management system, and (4) opportunities for improving the methodology of LCAs and LCCAs for future C&DW management. We find that enhancing the utility of extant LCAs and LCCAs in guiding technology deployment and policy decisions can be achieved by considering key parameters governing the techno-economic and environmental performance of C&DW management. In addition, it is critical to adopt and upscale emerging technologies to increase the added value of materials or products recovered from C&DW.